2021
DOI: 10.1111/os.12841
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of Human Skeleton Hardness Obtained Using the Micro‐indentation Technique

Abstract: Objectives: Measure and systematically evaluate the distribution of microhardness in the human skeleton.Methods: Three fresh corpses were obtained, aged 62 (male), 45 (female), and 58 years (male). Soft tissues were removed, and all axial and unilateral appendicular bones were freshly harvested. All three skeletons were examined by Xray and computed tomography (CT) to exclude skeletal pathology. Only bones from donors with no known skeletal pathology were included in the study. Axial and unilateral appendicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As one of the most important properties of bone, bone hardness includes elastic deformation and plastic deformation. The nanoindentation method was used to measure the hardness of human bones, which provided valuable data for the preparation of bone repair materials (Table 1) [19][20][21][22][23]. The bone has several irregular marrow cavities due to its structure.…”
Section: Mechanical Properties Of Natural Bonementioning
confidence: 99%
“…As one of the most important properties of bone, bone hardness includes elastic deformation and plastic deformation. The nanoindentation method was used to measure the hardness of human bones, which provided valuable data for the preparation of bone repair materials (Table 1) [19][20][21][22][23]. The bone has several irregular marrow cavities due to its structure.…”
Section: Mechanical Properties Of Natural Bonementioning
confidence: 99%
“…The hardest cortical bone hardness was in the range of 40-51.2 HV. 75 Hence, the LSP-treated Mg-1Zn-0.5Sc alloy can be beneficial for bone-implant application.…”
Section: Residual Stress and Microhardnessmentioning
confidence: 99%
“…To the best of our knowledge, the successful application of a hernia mesh wrapping an FA has only been introduced in a case report 23 . Three‐dimensional printing technology has promoted enormously the development of basic orthopedic investigations in the past decade 24–27 . However, relatively few studies based on this emerging technology have been conducted in clinical musculoskeletal oncology, in which major investigations focus on the reconstruction of the spine, pelvis and diarthrosis in the lower extremities 28–30 .…”
Section: Introductionmentioning
confidence: 99%
“…23 Three-dimensional printing technology has promoted enormously the development of basic orthopedic investigations in the past decade. [24][25][26][27] However, relatively few studies based on this emerging technology have been conducted in clinical musculoskeletal oncology, in which major investigations focus on the reconstruction of the spine, pelvis and diarthrosis in the lower extremities. [28][29][30] Based on a review of the relevant literature, 3D-printed prostheses have been preliminarily confirmed to be an acceptable option for en bloc resection of the distal radius, showing that when applying postoperative immobilization by 4 weeks to stabilize the joint, the occurrence of postoperative complications within or approximately 1 month after surgery was 33.3%.…”
Section: Introductionmentioning
confidence: 99%